Best-Worst Scaling: A New Method for Advertisement Evaluation - Massey, G.; Wang, P.; Waller, D.; Lanasier, Evi (Routledge, 2015)
The evaluation and selection of advertisements with desired levels of attributes such as ethicality, likeability, humour, or information content, can be undertaken using a variety of methods. These include researchers' personal judgments, focus groups, expert panels, and ratings scale approaches. However, there is still no generally accepted systematic evaluation or selection procedure. This paper details a simple but powerful method known as ‘best–worst scaling’ (BWS) to evaluate and select advertisements on criteria of interest. BWS represents an important new tool for advertising researchers, advertising agencies and their clients, communications scholars, and policy makers to evaluate and select advertisements. This paper achieves three ends. First, it critiques existing methods of advertisement evaluation. Second, it demonstrates that BWS has greater validity than existing methods. Third, this is the first paper to present a worked example of how to use BWS, and demonstrate its use in an advertisement evaluation context. Importantly, BWS is not restricted to evaluating advertisements – it can be used to evaluate any items on criteria of interest.